IMPLEMENTASI MARITIME LABOUR CONVENTION (MLC) TERHADAP HAK PELAUT PT. PELNI DI MASA PANDEMI COVID-19 TAHUN 2020-2022 - Bintani, Devioniza Sarah; Pakpahan, Saiman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This study explains the role of PT PELNI Tanjung Pinang to implements the Maritime Labour Convention (MLC) 2006 during the pandemic to protect seaferers’ rights and improve their welfare. The research further investigates the impact of the COVID-19 pandemic on seaferers’ well-being. In this case, MLC serves as and International convention that provides a standard framework for every ratifying country to ensure the welfare of seaferers through regulations and standarts adapted to the maritime industry. The research focuses on the implementation of health and safety procedures, crew changes policies, and efforts to support the mental and financial health of seaferers. This study employs a constructivist perspective based on the Regime Compliance. Arild Underdal identifies three variables used to analyze the effectiveness of a regime: the Dependent Variable, the Independent Variable, and the Intervening Variable. The level of analysis in this research is the nation-state, with a qualitative research method that includes literature review and interview for data collection. The result of this study show that PT PELNI successfully demonstrated its commitment to protecting seaferers’ rights during the pandemic, providing a relevant example for other maritime companies through the Optimization of Crew Changes, Seafarer Training and Education, and Seaferer Welfare. These optimization efforts are expected to strengthen the health and safety infrastructure in the maritime industry, preparing for similar challenges in the future. Keywords: COVID-19 Pandemic, PT PELNI, MLC 2006, Seaferer Protection, Maritime